Desarrollo sintáctico de una familia de construcciones con gana y fijación de las construcciones de indefinición con dar la gana - Ruiz Velasco Dávalos, Liliana (El Colegio de México, 2019)
The present study deals with the diachronic development in Classical and Modern Spanish of a familiy of syntactical constructions composed of the verb dar and the noun gana. For that matter data were collected from CORDE and a study was made of their basic semantic and syntactic features (roles, subject and complements), of their semantic differentiation, as well as of the constructions of which they formed part. The results point to a syntactic differentiation between the constructions and their use patterns, leading to one of them, dar la gana, being selected by speakers to form indefinite constructions.